Good Agricultural Practices (GAP) for improving rice productivity in Senegal - CGIAR Research Program on Rice (2021)
GAP modules have been developed based on field surveys on sustainable rice plateform indicators. 575 farmers including 162 women were trained on applying good agricultural practices for sustainable rice production over three years in Senegal.